Benefits of Head‐starting for Blanding's Turtle Size Distributions and Recruitment - Daniel Thompson; Gary Glowacki; Daniel Ludwig; Rachel Reklau; Andrew R. Kuhns; Callie Klatt Golba; Richard King (Wildlife Society Bulletin)
ABSTRACT Head‐starting is a widely used turtle conservation measure but its effectiveness is incompletely known. We evaluated the success of 2 long‐term Blanding's turtle (Emydoidea blandingii) head‐starting programs in northeastern Illinois, USA, focusing on the effect that head‐starting has on turtle population body‐size distributions and whether head‐started turtles are successfully recruited as reproductive adults. From 1994 to 2017, we collected and incubated eggs from wild females and reared hatchlings for release back into 2 source populations in DuPage and Lake counties, Illinois. Releases occurred annually for 21‐ and 11‐year spans (~1,400 and 800 releases, respectively). We found that head‐starting resulted in significant shifts in Blanding's turtle population body‐size distributions. Prior to intervention, size distributions were strongly skewed toward large adults at both sites, a pattern sometimes interpreted as arising from elevated egg and hatchling mortality and a lack of juvenile recruitment. Currently, population body‐size distributions include a wide range of juvenile and adult size turtles. Importantly, head‐starts have begun reproducing in the 21‐year program and are approaching adult size in the 11‐year program. Blanding's turtle head‐starting shows promise for increasing recruitment in existing populations while threat mitigation is implemented. © 2020 The Wildlife Society.